Palm Oil and Deforestation: Mapping the Scientific Debate through Bibliometric and Network Analysis (2000 – 2025) - Judijanto, Loso (West Science Agro, 2025)
The environmental impacts of palm oil cultivation—particularly its link to deforestation—have become the subject of growing global concern and academic inquiry. This study explores the scientific landscape of palm oil and deforestation research through a bibliometric and network analysis using data retrieved from the Scopus database. Employing VOSviewer, the analysis maps co-authorship networks, country collaborations, keyword co-occurrence, and thematic evolutions from 2017 to 2019. The findings reveal that research in this domain is highly interdisciplinary, with dominant themes centered on land use change, carbon emissions, biodiversity loss, and sustainability governance. Influential nodes include authors and institutions based in both producing countries (e.g., Indonesia and Malaysia) and research-intensive countries (e.g., United States and United Kingdom). Keyword trends also reflect a temporal shift from biophysical monitoring and remote sensing toward more integrative concerns such as certification, biofuels, and sustainable development. This study offers valuable insights for scholars, policymakers, and stakeholders by identifying knowledge gaps, highlighting collaborative opportunities, and providing a foundation for advancing sustainability discourse and action in the palm oil sector.